The Scientific and Cultural Journey to Ovarian Rejuvenation: Background, Barriers, and Beyond the Biological Clock - E. Scott Sills (Medicines, 2021)
Female age has been known to define reproductive outcome since antiquity; attempts to improve ovarian function may be considered against a sociocultural landscape that foreshadows current practice. Ancient writs heralded the unlikely event of an older woman conceiving as nothing less than miraculous. Always deeply personal and sometimes dynastically pivotal, the goal of achieving pregnancy often engaged elite healers or revered clerics for help. The sorrow of defeat became a potent motif of barrenness or miscarriage lamented in art, music, and literature. Less well known is that rejuvenation practices from the 1900s were not confined to gynecology, as older men also eagerly pursued methods to turn back their biological clock. This interest coalesced within the nascent field of endocrinology, then an emerging specialty. The modern era of molecular science is now offering proof-of-concept evidence to address the once intractable problem of low or absent ovarian reserve. Yet, ovarian rejuvenation by platelet-rich plasma (PRP) originates from a heritage shared with both hormone replacement therapy (HRT) and sex reassignment surgery. These therapeutic ancestors later developed into allied, but now distinct, clinical fields. Here, current iterations of intraovarian PRP are discussed with historical and cultural precursors centering on cell and tissue regenerative effects. Intraovarian PRP thus shows promise for women in menopause as an alternative to conventional HRT, and to those seeking pregnancy—either with advanced reproductive technologies or as unassisted conceptions.